Introducing teachers and administrators to the NGSS : a professional development facilitator's guide - Brunsell, Eric; Kneser, Deb M., 1955-; Niemi, Kevin J., 1956- (National Science Teachers Association, 2014)
If you and your students can't get enough of a good thing, Volume 2 of Uncovering Student Ideas in Physical Science is just what you need. The book offers 39 new formative assessment probes, this time with a focus on electric charge, electric current, and magnets and electromagnetism. It can help you do everything from demystify electromagnetic fields to explain the real reason balloons stick to the wall after you rub them on your hair.